Combined effects of quercetin and curcumin on anti-inflammatory and antimicrobial parameters in vitro - YALÇIN, AHMET SUHA (ELSEVIER, 2019)
In this in-vitro study, combinatory anti-inflammatory interactions between Quercetin (Q) and Curcumin (C) along with their combined antimicrobial activity against MRSA were studied. Anti-inflammatory markers of (i) COX-2 expression, (ii) NF kappa beta activation and (iii) NO levels were investigated. Antimicrobial synergy was tested by checkerboard assay. We found that, treatment with the low-concentration combination group (QC), where Q and C were combined, resulted in significant downregulation of COX-2 expression (P < 0.0001) and inhibition of NF kappa beta activation in cells (P < 0.0001), to a similar extent to that induced by higher concentrations of Q and C alone. QC treatment was also found to induce a significant reduction in NO production (P < 0.0001). QC was significantly more effective in the reduction of total NO levels when compared to Q alone (P < 0.001). Checkerboard assay indicated that the combination of Q and C provides better killing of MRSA in lower dilutions than standalone Minimum Inhibitory Concentrations. These results suggest that combining low concentrations of Q and C yield similar or better anti-inflammatory effectiveness when compared to treatment with each agent alone. Moreover, they co-operate synergistically in the context of antimicrobial activity, with an increased effectiveness when compared to Q or C alone at high concentrations.
Keywords: Quercetin; Curcumin; Anti-inflammatory; Antimicrobial; Synergy; ANTIBACTERIAL ACTIVITY